COVID-19 Vaccination in Patients with Classic Kaposi’s Sarcoma - Indini, Alice (Vaccines (Basel), 2021)
The novel coronavirus disease 2019 (COVID-19) has represented an overwhelming challenge for worldwide health systems. Patients with cancer are considered at higher risk for severe COVID-19 and increased mortality in case of infection. Although data on the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination in patients with cancer are limited, there is enough evidence supporting anti-infective vaccination in general in patients with active cancer, or with history of previous malignancy. Subjects with classic Kaposi’s sarcoma (KS) represent a small subset of cancer patients, which should be considered at heightened risk for infections due to several factors including age, and impaired immune function status. Several cases of human herpesviruses reactivation among critically ill COVID-19 patients have been described. Moreover, in case of severe infection and treatment with immunomodulating agents, patients with CKS are exposed at significant risk of viral reactivation and disease progression. Considering the baseline clinical risk factors of patients with CKS, and the complex interplay of the two viral agents, SARS-CoV-2 vaccination should be strongly recommended among patients with KS. KS represents an interesting field to study the interactions among chronic viral infections, SARS-CoV-2 and the host’s immune system. Prospective observational studies are needed to provide more insights on vaccine activity and safety among patients with cancer, optimal vaccine schedules, potential interactions with antineoplastic therapies, and other comorbidities including chronic viral infections.